Effect of slow breathing exercise on heart rate variability in tension-type headache female patients: A time domain analysis - Rahman, Shahanur; Sarkar, Nandita; Sheikh, Abdul Kader; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2022)
Background: Tension-type headache (TTH), the most frequently occurring primary headache is associated with autonomic dysfunction. Time domain analysis of heart rate variability (HRV) is a popular tool to detect changes in cardiac autonomic nerve function (CANF) in TTH patients. Slow breathing exercise (SBE) can significantly improve HRV in patients with cardiovascular disorders. Objective: To observe the effect of SBE on HRV by time domain analysis in TTH female patients. Methods: This quasi-experimental study was conducted from March 2021 to February 2022 in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka on 60 female TTH patients aged 20-45 years. Thirty patients performed SBE every morning and evening for 30 minutes in addition to receiving conventional treatment and 30 patients continued only conventional treatment without any exercise for 90 days. Thirty age, sex and BMI matched apparently healthy control were enrolled who did not perform SBE or any other exercise. All subjects were assessed at baseline and also after 90 days. Time domain HRV parameters were recorded by Power Lab 8/35 AD Instruments, Australia. One way ANOVA followed by post-hoc test and Paired sample t-test were performed for statistical analysis and p<0.05 was considered as statistical significance. Results: Mean heart rate (HR) was significantly higher (p<0.001) and SDRR (Standard deviation of all RR interval); CVRR (Coefficient variation of RR interval); SDSD (Standard deviation of successive RR interval differences between adjacent RR intervals); RMSSD (Square root of mean of squared differences of successive RR interval) and pRR50% (Proportion of RR interval with duration > 50ms) were significantly lower (p<0.001) in TTH female patients compared to control at baseline. Significant decrement of mean HR (p<0.001) and increment of all other time domain parameters (p<0.001) was observed after 90 days of SBE. Again, significantly decreased SDRR, CVRR, SDSD, RMSSD and pRR50% (p<0.001, p<0.01) was observed in the patients who did not perform SBE. Conclusion: SBE may effectively improve cardiac autonomic dysfunction in TTH female patients. J Bangladesh Soc Physiol. 2022, June; 17(1): 56-63